Preparation method of high-performance ceramic filler
By dividing zirconia powder into components of different particle sizes and subjecting to corrosion and electrostatic treatment, it forms a rich pore structure, which solves the problem of lack of pores on the surface of ceramic fillers, significantly improves its specific surface area and porosity performance, and improves compressive and tensile strength.
Patent Information
- Application Number
- CN202411946269.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-11
AI Technical Summary
In the processing process, the existing ceramic fillers have smooth surfaces and lack pore structures due to ball milling, which show poor specific surface area and porosity performance.
By dividing the zirconia powder into components A and components B with different particle sizes, component B is corroded and formed a rich pore structure. Component A is subjected to a positive charge after electrostatic treatment. Electrostatic attraction is used to uniformly adsorb component A powder on the surface of component B powder, forming a zirconia powder raw material with high specific surface area and porosity.
The specific surface area and porosity performance of ceramic fillers are significantly improved, and they have excellent compressive strength and tensile strength properties.
Smart Images

Figure CN119793386A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ceramic fillers, in particular to a method for preparing a high-performance ceramic filler. Background Art
[0002] Ceramic filler is a material widely used in many fields such as chemical industry and environmental protection. Ceramic filler is a solid filler made of ceramic material used to fill various towers. Its purpose is to increase the gas-liquid contact area and make the gas-liquid two phases fully contact on the filler surface, thereby improving the mass transfer and heat transfer efficiency.
[0003] In the prior art, the specific surface area and porosity data of ceramic fillers are key factors affecting the performance of ceramic fillers. However, in the existing processing flow of ceramic fillers, the powder used as raw materials needs to be ball-milled. The surface of the powdered raw materials after ball-milling will be relatively smooth, so that the surface of the ceramic filler formed after the powder combination lacks a pore structure, and the specific surface area and porosity performance are poor. Based on this, the present invention provides a preparation method for high-performance ceramic fillers. Summary of the invention
[0004] The purpose of the present invention is to provide a method for preparing a high-performance ceramic filler. The high-performance ceramic filler prepared by the present invention not only has good specific surface area and porosity performance, but also has excellent compressive strength and tensile strength performance, which effectively improves the performance of the ceramic filler.
[0005] To achieve the above object, the present invention provides the following technical solution: a method for preparing a high-performance ceramic filler, comprising the following steps:
[0006] S1: Raw material preparation, selecting zirconium oxide powder as raw material, and dividing the raw material into component A and component B, wherein the particle size of the zirconium oxide powder of component A is 4 μm, the particle size of the zirconium oxide powder of component B is 20 μm, and the mass ratio of component A to component B is 2:8;
[0007] S2: Corrosion treatment, corroding the zirconium oxide powder of component B;
[0008] S3: electrostatic treatment, electrostatic treatment of the zirconium oxide powder of component A;
[0009] S4: preparing a mixture, mixing the zirconium oxide powder of component A that has been electrostatically treated with the zirconium oxide powder of component B that has been corrosion treated to prepare a mixture;
[0010] S5: Preparation of additives;
[0011] S6: Firing treatment, processing the mixed material and the additive to obtain a ceramic filler.
[0012] Furthermore, the method for corrosion treatment is: sending the B component zirconium oxide powder into an oven, setting the temperature to 60-70°C for drying for 40-50 minutes, pouring the dried zirconium oxide powder into an autoclave, pouring a corrosion liquid into the autoclave, wherein the mass of the corrosion liquid is 1.2-1.4 times the mass of the B component zirconium oxide powder, the temperature is set to 120-140°C, the pressure is 6-10MPa, reacting under high pressure and high temperature conditions for 2-4 hours, taking out the B component zirconium oxide powder after the reaction, rinsing it with deionized water for 5-7 times, draining the water and sending it into an oven, setting the temperature to 60-70°C for drying for 20-30 minutes, and completing the corrosion treatment of the B component zirconium oxide powder.
[0013] Furthermore, the etching solution is composed of the following raw materials: hydrofluoric acid solution, sodium dodecyl sulfate solution and oxalic acid, the mass ratio of the hydrofluoric acid solution, sodium dodecyl sulfate solution and oxalic acid is 1:(0.4-0.6):(0.2-0.4), the concentration of the hydrofluoric acid solution is 2-4 mol / L, the concentration of the sodium dodecyl sulfate solution is 0.2-0.4 mol / L, and the concentration of the oxalic acid is 0.6-0.8 mol / L.
[0014] Furthermore, the etching solution is prepared by the following method: mixing hydrofluoric acid solution and sodium dodecyl sulfate solution into a mixer, setting the mixer to 60-80 r / min and stirring for 4-6 minutes, adding oxalic acid after stirring, setting 120-140 r / min and continuing stirring for 6-8 minutes to prepare the etching solution.
[0015] Furthermore, the electrostatic treatment method is: spreading the A component zirconium oxide powder in a tray with a thickness of 1 to 3 mm, sending the tray into a plasma treatment instrument, setting the power to 100 to 200 W, the treatment time to 3 to 5 minutes, and introducing argon gas during the treatment process.
[0016] Furthermore, the mixing treatment method is: adding the A component zirconium oxide powder that has completed the electrostatic treatment and the B component zirconium oxide powder that has completed the corrosion treatment into a mixer, setting 50 to 60 r / min and stirring for 20 to 30 minutes to obtain a mixture.
[0017] Furthermore, the additive is composed of the following raw materials: anhydrous ethanol, silicon dioxide, magnesium fluorosilicate and silicon carbide, the mass ratio of the anhydrous ethanol, silicon dioxide, magnesium fluorosilicate and silicon carbide is 10: (1.2-1.6): (0.6-0.8): (0.4-0.6), and the mass of the additive is 3 times the mass of the mixture.
[0018] Furthermore, the additive is prepared by the following method: the anhydrous ethanol, silicon dioxide, magnesium fluorosilicate and silicon carbide are added to a mixer, the mixer is set to 300-400r / min and stirred for 10-20min, after the stirring is completed, the mixture in the mixer is added to an ultrasonic disperser, set to 60-80kHz and processed for 20-30min to prepare the additive.
[0019] Furthermore, the silicon dioxide, magnesium fluorosilicate and silicon carbide have a particle size of ≤15 μm.
[0020] Furthermore, the firing treatment method is:
[0021] Step 1: The mixed material and the additive are fed into a mixer, set at 50-60 r / min and stirred for 20-30 min to obtain a mud material, which is then fed into a filter press to remove moisture;
[0022] Step 2: The mud after the filter press treatment is sent to a vacuum mud kneader for 8 to 10 hours, and then sent to a drying box after being left to stand for 10 days, and treated at 120 to 160°C for 40 to 50 minutes to obtain dry mud;
[0023] Step 3: The dried clay is sent into a kiln with a set temperature of 1200-1400°C for 2-4 hours, then cooled to 700-800°C for 1-3 hours, and taken out after cooling to obtain a high-performance ceramic filler.
[0024] Compared with the prior art, the present invention has the following beneficial effects:
[0025] 1. In the present invention, the zirconium oxide powder as the main material is divided into two components AB with different particle sizes. After the larger amount of fine powder is corroded, the surface of the B component powder is corroded to form a rich pore structure. By adding sodium dodecyl sulfate in the corrosive solution, the fine powder component is given a negative charge, and the smaller amount of ultrafine powder component A is given a positive charge after being treated by a plasma treatment instrument. Since the zirconium oxide powders of the AB components have opposite charges, the electrostatic attraction can be used to promote the ultrafine powder to be uniformly adsorbed on the surface of the fine powder, that is, the zirconium oxide powders of the two components can be combined with each other to form a zirconium oxide powder raw material with very rich surface pores, thereby improving the specific surface area and porosity performance of the ceramic filler.
[0026] 2. In the present invention, by mixing hydrofluoric acid solution, sodium dodecyl sulfate solution and oxalic acid in the etching solution, the surface of the zirconium oxide powder is corroded by utilizing the corrosive properties of the hydrofluoric acid solution and the sodium dodecyl sulfate solution. A rich pore structure is formed on the surface of the corroded zirconium oxide powder. Oxalic acid can form new coordination bonds with zirconium ions to form trioxalatozirconate ions. The trioxalatozirconate ions stretch and distort the chemical bonds between zirconium ions and oxygen ions, thereby reducing the structural stability of the zirconium oxide and accelerating the corrosion process. The surface corrosion of the zirconium oxide can be completed quickly, and excessive weight loss of the zirconium oxide powder caused by long-term corrosion treatment can be avoided.
[0027] 3. In the present invention, silicon dioxide, magnesium fluorosilicate and silicon carbide are used in combination, wherein silicon dioxide can form a skeleton structure in the ceramic filler obtained by sintering, thereby improving the strength of the ceramic filler, and magnesium fluorosilicate can act as a flux to help silicon dioxide, magnesium fluorosilicate and silicon carbide to undergo sintering reaction at a relatively low temperature. The skeleton structure constructed by silicon dioxide provides a good foundation for the filling of magnesium fluorosilicate and the dispersion of silicon carbide. Magnesium fluorosilicate is filled in the gaps formed by silicon dioxide and zirconium oxide, thereby making the structure of the ceramic filler obtained by sintering more compact, thereby achieving the purpose of improving the overall structural strength of the ceramic filler. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 The invention proposes a flow chart of a method for preparing a high-performance ceramic filler. DETAILED DESCRIPTION
[0029] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0030] In order to enable those skilled in the art to better understand the solution of the present application, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the accompanying drawings.
[0031] This embodiment provides a method for preparing a high-performance ceramic filler, comprising the following steps:
[0032] S1: Raw material preparation, selecting zirconium oxide powder as raw material, and dividing the raw material into component A and component B, the particle size of the zirconium oxide powder of component A is 4 μm, the particle size of the zirconium oxide powder of component B is 20 μm, and the mass ratio of component A to component B is 2:8;
[0033] S2: Corrosion treatment, corroding the zirconium oxide powder of component B;
[0034] S3: electrostatic treatment, electrostatic treatment of the zirconium oxide powder of component A;
[0035] S4: preparing a mixture, mixing the zirconium oxide powder of component A that has been electrostatically treated with the zirconium oxide powder of component B that has been corrosion treated to prepare a mixture;
[0036] S5: Preparation of additives;
[0037] S6: Firing treatment, processing the mixed material and the additive to obtain a ceramic filler.
[0038] In some embodiments, the method of corrosion treatment is: sending the B component zirconium oxide powder into an oven, setting the temperature to 60-70°C for drying for 40-50 minutes, pouring the dried zirconium oxide powder into an autoclave, pouring a corrosion liquid into the autoclave, the mass of the corrosion liquid is 1.2-1.4 times the mass of the B component zirconium oxide powder, setting the temperature to 120-140°C, the pressure to 6-10MPa, reacting under high pressure and high temperature conditions for 2-4 hours, taking out the B component zirconium oxide powder after the reaction, rinsing it with deionized water for 5-7 times, draining the water and sending it into an oven, setting the temperature to 60-70°C for drying for 20-30 minutes, and completing the corrosion treatment of the B component zirconium oxide powder.
[0039] In this embodiment, the surface of the zirconium oxide powder is corroded by utilizing the corrosive properties of the hydrofluoric acid solution and the sodium dodecyl sulfate solution, and a rich porous structure is formed on the surface of the corroded zirconium oxide powder.
[0040] In some embodiments, the etching solution is composed of the following raw materials: hydrofluoric acid solution, sodium dodecyl sulfate solution and oxalic acid, the mass ratio of hydrofluoric acid solution, sodium dodecyl sulfate solution and oxalic acid is 1:(0.4-0.6):(0.2-0.4), the concentration of hydrofluoric acid solution is 2-4 mol / L, the concentration of sodium dodecyl sulfate solution is 0.2-0.4 mol / L, and the concentration of oxalic acid is 0.6-0.8 mol / L.
[0041] In this embodiment, oxalic acid can form new coordination bonds with zirconium ions to form trioxalatozirconate ions. The trioxalatozirconate ions stretch and distort the chemical bonds between the zirconium ions and the oxygen ions, thereby reducing the structural stability of zirconium oxide and accelerating the corrosion process. The surface corrosion of zirconium oxide can be completed quickly, avoiding excessive weight loss of zirconium oxide powder due to long-term corrosion treatment.
[0042] In some embodiments, the etching liquid is prepared by the following method: mixing hydrofluoric acid solution and sodium dodecyl sulfate solution into a mixer, setting the mixer to stir at 60-80 r / min for 4-6 minutes, adding oxalic acid after stirring, setting the mixer to stir at 120-140 r / min for 6-8 minutes, and preparing the etching liquid.
[0043] In this embodiment, by adding sodium dodecyl sulfate to the etching solution, the sulfate ions in the sodium dodecyl sulfate react with the hydroxyl groups on the surface of zirconium oxide through electrostatic attraction and chemical adsorption, thereby imparting a negative charge to the fine powder component.
[0044] In some embodiments, the electrostatic treatment method is: spreading the A component zirconium oxide powder in a tray with a thickness of 1 to 3 mm, sending the tray into a plasma treatment instrument, setting the power to 100 to 200 W, the treatment time to 3 to 5 minutes, and introducing argon gas during the treatment process.
[0045] In this embodiment, the ultrafine powder component A with a smaller amount is given a positive charge after being processed by a plasma treatment apparatus.
[0046] In some embodiments, the mixing method is: add the zirconium oxide powder of component A that has been electrostatically treated and the zirconium oxide powder of component B that has been corrosion treated into a mixer, set the mixer to 50 to 60 r / min and stir for 20 to 30 minutes to obtain a mixture.
[0047] In this embodiment, since the zirconium oxide powders of the AB components carry opposite charges, electrostatic attraction can be used to cause the ultrafine powder to be evenly adsorbed on the surface of the fine powder, that is, the zirconium oxide powders of the two components can combine with each other to form a zirconium oxide powder raw material with very rich surface pores, thereby improving the specific surface area and porosity performance of the ceramic filler.
[0048] In some embodiments, the additive is composed of the following raw materials: anhydrous ethanol, silicon dioxide, magnesium fluorosilicate and silicon carbide, the mass ratio of anhydrous ethanol, silicon dioxide, magnesium fluorosilicate and silicon carbide is 10: (1.2~1.6): (0.6~0.8): (0.4~0.6), and the mass of the additive is 3 times the mass of the mixture.
[0049] In some embodiments, the additive is prepared by the following method: anhydrous ethanol, silicon dioxide, magnesium fluorosilicate and silicon carbide are added to a mixer, the mixer is set to 300-400 r / min and stirred for 10-20 minutes, after the stirring is completed, the mixture in the mixer is added to an ultrasonic disperser, set to 60-80 kHz and processed for 20-30 minutes to obtain the additive.
[0050] In this embodiment, silicon dioxide can form a skeleton structure in the ceramic filler formed by sintering, which plays a role in improving the strength of the ceramic filler. Magnesium fluorosilicate can act as a flux to help silicon dioxide, magnesium fluorosilicate and silicon carbide to undergo sintering reaction at a lower temperature. The skeleton structure constructed by silicon dioxide provides a good foundation for the filling of magnesium fluorosilicate and the dispersion of silicon carbide. Magnesium fluorosilicate is filled in the gaps formed by silicon dioxide and zirconium oxide, making the structure of the ceramic filler formed by sintering more dense, thereby achieving the purpose of improving the overall structural strength of the ceramic filler.
[0051] In some embodiments, silicon dioxide, magnesium fluorosilicate, and silicon carbide are selected to have a particle size of ≤15 μm.
[0052] In some embodiments, the firing process is:
[0053] Step 1: The mixed material and the additive are sent to the mixer, set at 50-60r / min and stirred for 20-30min to obtain the mud material, which is then sent to the filter press to remove moisture;
[0054] Step 2: The mud after the filter press treatment is sent to a vacuum mud kneader for 8 to 10 hours, and then sent to a drying box after being left to stand for 10 days, and treated at 120 to 160°C for 40 to 50 minutes to obtain dry mud;
[0055] Step 3: The dried clay is sent into a kiln with a set temperature of 1200-1400°C for 2-4 hours, then cooled to 700-800°C for 1-3 hours, and taken out after cooling to obtain a high-performance ceramic filler.
[0056] Based on the above embodiments, the inventors also conducted the following experiments:
[0057] It should be noted that the raw materials used in the following experiments are all commercially available raw materials.
[0058] Experiment 1:
[0059] Zirconia powder was selected as the raw material, and the raw material was divided into component A and component B. The particle size of the zirconia powder of component A was 4 μm, the particle size of the zirconia powder of component B was 20 μm, and the mass ratio of component A to component B was 2:8.
[0060] Preparation of etching solution: Mix hydrofluoric acid solution and sodium dodecyl sulfate solution and add them into a mixer, set the mixer to stir at 60 r / min for 4 min, add oxalic acid after stirring, set the mixer to stir at 120 r / min for 6 min, the mass ratio of hydrofluoric acid solution, sodium dodecyl sulfate solution and oxalic acid is 1:0.4:0.2, the concentration of hydrofluoric acid solution is 2 mol / L, the concentration of sodium dodecyl sulfate solution is 0.2 mol / L, and the concentration of oxalic acid is 0.6 mol / L;
[0061] Preparation of additives: anhydrous ethanol, silicon dioxide, magnesium fluorosilicate and silicon carbide are added to a mixer, and the mixer is set to 300r / min and stirred for 10 minutes. After the stirring is completed, the mixture in the mixer is added to an ultrasonic disperser, and the mixture is set to 60kHz for 20 minutes. The mass ratio of anhydrous ethanol, silicon dioxide, magnesium fluorosilicate and silicon carbide is 10:1.2:0.6:0.4, and the particle size of silicon dioxide, magnesium fluorosilicate and silicon carbide is selected to be ≤15μm;
[0062] The B component zirconium oxide powder was placed in an oven and dried at 60°C for 40 minutes. The dried zirconium oxide powder was poured into an autoclave, and a corrosive solution was poured into the autoclave. The mass of the corrosive solution was 1.2 times the mass of the B component zirconium oxide powder. The temperature was set to 120°C and the pressure was 6MPa. The reaction was carried out under high pressure and high temperature conditions for 2 hours. After the reaction was completed, the B component zirconium oxide powder was taken out, rinsed with deionized water for 5 times, drained, and placed in an oven, and dried at 60°C for 20 minutes.
[0063] The zirconium oxide powder of component A was spread flat on a tray with a thickness of 1 mm. The tray was placed in a plasma treatment instrument with a power of 100 W and a treatment time of 3 min. Argon gas was introduced during the treatment process.
[0064] The zirconium oxide powder of component A that has been electrostatically treated and the zirconium oxide powder of component B that has been corrosion treated are added into a mixer, and stirred at 50 r / min for 20 min to obtain a mixture;
[0065] Preparation of ceramic filler: The mixture and additives are sent to a mixer and stirred at 50r / min for 20min to obtain mud. The mud is sent to a filter press to remove moisture. The mud after filter pressing is sent to a vacuum mud kneading machine for treatment for 8h. After standing for 10 days, it is sent to a drying box and set at 120℃ for treatment for 40min to obtain dry mud. The dry mud is sent to a kiln with a set temperature of 1200℃ for 2h. The temperature is then reduced to 700℃ for 1h. It is taken out after cooling to obtain high-performance ceramic filler.
[0066] Experiment 2:
[0067] Zirconia powder was selected as the raw material, and the raw material was divided into component A and component B. The particle size of the zirconia powder of component A was 4 μm, the particle size of the zirconia powder of component B was 20 μm, and the mass ratio of component A to component B was 2:8.
[0068] Preparation of etching solution: Mix hydrofluoric acid solution and sodium dodecyl sulfate solution and add them into a mixer, set the mixer to stir at 70 r / min for 5 min, add oxalic acid after stirring, set the mixer to stir at 130 r / min for 7 min, the mass ratio of hydrofluoric acid solution, sodium dodecyl sulfate solution and oxalic acid is 1:0.5:0.3, the concentration of hydrofluoric acid solution is 3 mol / L, the concentration of sodium dodecyl sulfate solution is 0.3 mol / L, and the concentration of oxalic acid is 0.7 mol / L;
[0069] Preparation of additives: anhydrous ethanol, silicon dioxide, magnesium fluorosilicate and silicon carbide are added to a mixer, and the mixer is set to 350r / min and stirred for 15 minutes. After the stirring is completed, the mixture in the mixer is added to an ultrasonic disperser, and the mixture is set to 70kHz and processed for 25 minutes. The mass ratio of anhydrous ethanol, silicon dioxide, magnesium fluorosilicate and silicon carbide is 10:1.4:0.7:0.5, and the particle size of silicon dioxide, magnesium fluorosilicate and silicon carbide is selected to be ≤15μm;
[0070] The B component zirconium oxide powder was placed in an oven and dried at 65°C for 45 minutes. The dried zirconium oxide powder was poured into an autoclave, and a corrosive solution was poured into the autoclave. The mass of the corrosive solution was 1.3 times the mass of the B component zirconium oxide powder. The temperature was set to 130°C and the pressure was 8MPa. The reaction was carried out under high pressure and high temperature conditions for 3 hours. After the reaction was completed, the B component zirconium oxide powder was taken out, rinsed with deionized water for 6 times, drained, and placed in an oven, and dried at 65°C for 25 minutes.
[0071] The zirconium oxide powder of component A was spread flat on a tray with a thickness of 2 mm. The tray was placed in a plasma treatment instrument with a power set to 150 W and a treatment time of 4 min. Argon gas was introduced during the treatment process.
[0072] The zirconium oxide powder of component A that has been electrostatically treated and the zirconium oxide powder of component B that has been corrosion treated are added into a mixer, and stirred at 55 r / min for 25 min to obtain a mixture;
[0073] Preparation of ceramic filler: The mixture and additives are sent to a mixer and stirred at 55r / min for 25min to obtain mud. The mud is sent to a filter press to remove moisture. The mud after filter pressing is sent to a vacuum mud kneading machine for treatment for 9h. After standing for 10 days, it is sent to a drying box and set to 140℃ for treatment for 45min to obtain dry mud. The dry mud is sent to a kiln with a set temperature of 1300℃ for 3h. The temperature is then reduced to 750℃ and kept for 2h. After cooling, it is taken out to obtain high-performance ceramic filler.
[0074] Experiment 3:
[0075] Zirconia powder was selected as the raw material, and the raw material was divided into component A and component B. The particle size of the zirconia powder of component A was 4 μm, the particle size of the zirconia powder of component B was 20 μm, and the mass ratio of component A to component B was 2:8.
[0076] Preparation of etching solution: Mix hydrofluoric acid solution and sodium dodecyl sulfate solution and add them into a mixer, set the mixer to 80 r / min and stir for 6 min, add oxalic acid after stirring, set 140 r / min and continue stirring for 8 min, the mass ratio of hydrofluoric acid solution, sodium dodecyl sulfate solution and oxalic acid is 1:0.6:0.4, the concentration of hydrofluoric acid solution is 4 mol / L, the concentration of sodium dodecyl sulfate solution is 0.4 mol / L, and the concentration of oxalic acid is 0.8 mol / L;
[0077] Preparation of additives: anhydrous ethanol, silicon dioxide, magnesium fluorosilicate and silicon carbide are added to a mixer, and the mixer is set to 400r / min and stirred for 20min. After the stirring is completed, the mixture in the mixer is added to an ultrasonic disperser, and the mixture is set to 80kHz and processed for 30min. The mass ratio of anhydrous ethanol, silicon dioxide, magnesium fluorosilicate and silicon carbide is 10:1.6:0.8:0.6, and the particle size of silicon dioxide, magnesium fluorosilicate and silicon carbide is selected to be ≤15μm;
[0078] The B component zirconium oxide powder was placed in an oven and dried at 70°C for 50 minutes. The dried zirconium oxide powder was poured into an autoclave, and a corrosive solution was poured into the autoclave. The mass of the corrosive solution was 1.4 times the mass of the B component zirconium oxide powder. The temperature was set to 140°C and the pressure was 10MPa. The reaction was carried out under high pressure and high temperature conditions for 4 hours. After the reaction was completed, the B component zirconium oxide powder was taken out, rinsed with deionized water for 7 times, drained, and placed in an oven. The dried solution was set to 70°C for 30 minutes.
[0079] The zirconium oxide powder of component A was spread flat on a tray with a thickness of 3 mm. The tray was placed in a plasma treatment instrument with a power of 200 W and a treatment time of 5 min. Argon gas was introduced during the treatment process.
[0080] The zirconium oxide powder of component A that has been electrostatically treated and the zirconium oxide powder of component B that has been corrosion treated are added into a mixer, and stirred at 60 r / min for 30 min to obtain a mixture;
[0081] Preparation of ceramic filler: The mixture and additives are sent to a mixer and stirred at 60r / min for 30 minutes to obtain mud. The mud is sent to a filter press to remove moisture. The mud after filter pressing is sent to a vacuum mud kneading machine for treatment for 10 hours. After standing for 10 days, it is sent to a drying box and set to 160℃ for treatment for 50 minutes to obtain dry mud. The dry mud is sent to a kiln with a set temperature of 1400℃ for 4 hours. The temperature is then reduced to 800℃ and kept for 3 hours. After cooling, it is taken out to obtain high-performance ceramic filler.
[0082] Comparative Example 1: The difference between this comparative example and Experiment 1 is that:
[0083] No corrosion treatment was performed in this comparative example.
[0084] Comparative Example 2: The difference between this comparative example and Experiment 1 is that:
[0085] This comparative example was not subjected to electrostatic treatment.
[0086] Comparative Example 3: The difference between this comparative example and Experiment 1 is that:
[0087] This comparative example does not contain any additives.
[0088] Comparative Example 4: The difference between this comparative example and Experiment 1 is that:
[0089] In this comparative example, the zirconium oxide powder was not grouped.
[0090] Performance test: The ceramic fillers prepared in Experiment 1, Experiment 2, Experiment 3, Comparative Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 4 were tested for performance, and the test data obtained are recorded in the following table:
[0091]
[0092] Among them, the specific surface area data of the ceramic fillers prepared in Experiment 1, Experiment 2, Experiment 3, Comparative Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 4 are 156m 2 、151m 2 、149m 2 、121m 2 、116m 2 、108m 2 and 115m 2 ;
[0093] The porosity data of the ceramic fillers prepared in Experiment 1, Experiment 2, Experiment 3, Comparative Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 4 are 98.5%, 98.6%, 97.9%, 84.3%, 80.6%, 76.3% and 77.5%, respectively;
[0094] The compressive strength data of the ceramic fillers prepared in Experiment 1, Experiment 2, Experiment 3, Comparative Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 4 are 31MPa, 30MPa, 32MPa, 18MPa, 17MPa, 13MPa and 15MPa respectively;
[0095] The tensile strength data of the ceramic fillers prepared in Experiment 1, Experiment 2, Experiment 3, Comparative Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 4 are 7.5 MPa, 7.6 MPa, 6.9 MPa, 5.1 MPa, 5.2 MPa, 4.3 MPa and 3.9 MPa, respectively.
[0096] It can be seen that the specific surface area, porosity, compressive strength and tensile strength data of the ceramic fillers prepared in Comparative Examples 1, 2, 3 and 4 are all lower than those in Experiments 1, 2 and 3; this shows that: by dividing the zirconium oxide powder as the main ingredient into two components AB with different particle sizes, the larger amount of fine powder is corroded, and the surface of the B component powder is corroded to form a rich pore structure. By adding sodium dodecyl sulfate in the corrosive liquid, the fine powder component is given a negative charge, and the smaller amount of ultrafine powder component A is given a positive charge after being treated by a plasma treatment instrument. Since the zirconium oxide powders of the AB components carry opposite charges, electrostatic attraction can be used to promote the uniform adsorption of the ultrafine powder on the surface of the fine powder, that is, the zirconium oxide powders of the two components can combine with each other to form a zirconium oxide powder raw material with very rich surface pores, thereby improving the specific surface area and porosity performance of the ceramic filler.
[0097] By comparing and analyzing the relevant data in the table, it can be seen that the high-performance ceramic filler prepared by the present invention not only has good specific surface area and porosity performance, but also has excellent compressive strength and tensile strength performance. This shows that the preparation method of the high-performance ceramic filler provided by the present invention has a broader market prospect and is more suitable for promotion.
[0098] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0099] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. A method for preparing a high-performance ceramic filler, characterized in that: The following steps are involved: S1: Raw material preparation, selecting zirconium oxide powder as raw material, and dividing the raw material into component A and component B, wherein the particle size of the zirconium oxide powder of component A is 4 μm, the particle size of the zirconium oxide powder of component B is 20 μm, and the mass ratio of component A to component B is 2:8; S2: Corrosion treatment, corroding the zirconium oxide powder of component B; S3: electrostatic treatment, electrostatic treatment of the zirconium oxide powder of component A; S4: preparing a mixture, mixing the zirconium oxide powder of component A that has been electrostatically treated with the zirconium oxide powder of component B that has been corrosion treated to prepare a mixture; S5: Preparation of additives; S6: sintering treatment, processing the mixed material and the additive to obtain a ceramic filler.
2. The method for preparing a high performance ceramic filler according to claim 1, characterized in that: The method for the corrosion treatment is as follows: the B component zirconium oxide powder is put into an oven, set at 60-70° C. for drying for 40-50 minutes, the dried zirconium oxide powder is poured into an autoclave, and a corrosion liquid is poured into the autoclave, wherein the mass of the corrosion liquid is 1.2-1.4 times the mass of the B component zirconium oxide powder, the temperature is set at 120-140° C., the pressure is 6-10 MPa, and the reaction is carried out under high pressure and high temperature conditions for 2-4 hours. After the reaction is completed, the B component zirconium oxide powder is taken out, rinsed with deionized water for 5-7 times, drained, and put into an oven, set at 60-70° C. for drying for 20-30 minutes, and the corrosion treatment of the B component zirconium oxide powder is completed.
3. The method for preparing a high performance ceramic filler according to claim 2, characterized in that: The etching solution is composed of the following raw materials: hydrofluoric acid solution, sodium dodecyl sulfate solution and oxalic acid, the mass ratio of the hydrofluoric acid solution, sodium dodecyl sulfate solution and oxalic acid is 1:(0.4-0.6):(0.2-0.4), the concentration of the hydrofluoric acid solution is 2-4 mol / L, the concentration of the sodium dodecyl sulfate solution is 0.2-0.4 mol / L, and the concentration of the oxalic acid is 0.6-0.8 mol / L.
4. The method for preparing a high performance ceramic filler according to claim 3, characterized in that: The etching solution is prepared by the following method: mixing hydrofluoric acid solution and sodium dodecyl sulfate solution into a mixer, setting the mixer to stir at 60-80 r / min for 4-6 min, adding oxalic acid after stirring, setting the mixer to stir at 120-140 r / min for 6-8 min, and preparing the etching solution.
5. The method for preparing a high performance ceramic filler according to claim 1, characterized in that: The electrostatic treatment method is as follows: the A component zirconium oxide powder is spread flat in a tray with a thickness of 1 to 3 mm, the tray is sent into a plasma treatment instrument, the power is set to 100 to 200 W, the treatment time is 3 to 5 minutes, and argon gas is introduced during the treatment process.
6. The method for preparing a high performance ceramic filler according to claim 1, characterized in that: The mixing method comprises: adding the zirconium oxide powder of component A which has been electrostatically treated and the zirconium oxide powder of component B which has been corrosion treated into a mixer, setting the stirring speed at 50 to 60 r / min for 20 to 30 minutes, and obtaining a mixture.
7. The method for preparing a high performance ceramic filler according to claim 1, characterized in that: The additive is composed of the following raw materials: anhydrous ethanol, silicon dioxide, magnesium fluorosilicate and silicon carbide, the mass ratio of the anhydrous ethanol, silicon dioxide, magnesium fluorosilicate and silicon carbide is 10: (1.2-1.6): (0.6-0.8): (0.4-0.6), and the mass of the additive is 3 times the mass of the mixture.
8. The method for preparing a high performance ceramic filler according to claim 7, characterized in that: The additive is prepared by the following method: the anhydrous ethanol, silicon dioxide, magnesium fluorosilicate and silicon carbide are added into a mixer, the mixer is set at 300-400 r / min and stirred for 10-20 min, after the stirring is completed, the mixture in the mixer is added into an ultrasonic disperser, set at 60-80 kHz and processed for 20-30 min to prepare the additive.
9. The method for preparing a high performance ceramic filler according to claim 8, characterized in that: The silicon dioxide, magnesium fluorosilicate and silicon carbide have a particle size of ≤15 μm.
10. The method for preparing a high performance ceramic filler according to claim 1, characterized in that: The method of the firing treatment is: Step 1: The mixed material and the additive are fed into a mixer, set at 50-60 r / min and stirred for 20-30 min to obtain a mud material, which is then fed into a filter press to remove moisture; Step 2: The mud after the filter press treatment is sent to a vacuum mud kneader for 8 to 10 hours, and then sent to a drying box after being left to stand for 10 days, and treated at 120 to 160°C for 40 to 50 minutes to obtain dry mud; Step 3: The dried clay is sent into a kiln with a set temperature of 1200-1400°C for 2-4 hours, then cooled to 700-800°C for 1-3 hours, and taken out after cooling to obtain a high-performance ceramic filler.
Citation Information
Cited By
Method for detecting opening uniformity of high-performance ceramic filler
CN115639130A
A method for detecting the uniformity of openings in high-performance ceramic fillers
CN115639130B